PENGARUH RISIKO KREDIT DAN RISIKO PASAR TERHADAP TINGKAT PROFITABILITAS (ROA) - banurea, saydan nikodemus; Manda, Gusganda Suria (COMPETITIVE, 2023)
At this time, commercial banks are very helpful for the development of the Indonesian economy because almost all people use banking services. In a banking sector, it will definitely try to avoid external and internal risks. The aim of this research is to know either simultaneously or partially. In this study, the selected sample was BNI (Bank Negara Indonesia) for the period 2012-2019. The data collection technique in this study was secondary data. The analytical method used is multiple linear analysis using SPSS 25. The results of this study are credit risk and market risk have a significant effect simultaneously on profitability. The results showed that: (1) credit risk has a negative effect on profitability, this can be proven by 0.006 <0.05 and the t value of -1.102 <1.697. (2) Based on the results of the partial t test, it can be concluded that market risk has a sig value of 0.202> 0.05 and a value of t count -1.300 <2.032. So it can be concluded that market risk has a negative and significant effect on profitability. (3) simultaneous credit risk and market risk have a sig 0.20> 0.05 and the F count is 4.406> 3.28, it can be concluded that the variable credit risk and market risk simultaneously have a positive effect on profitability (ROA).